The Experience of the Upu Smurd Floreasca Team during the Earthquakes in Turkey, February 2023 - Bogdan Oprita; Ruxandra Oprita; Teodor-Nicolae Berea; Ionut Olaru; Marian Alexandru Draghici (Emergency Care and Medicine)
Background: The recent earthquakes that occurred in Southern Turkey on the 6th of February 2023, were the most devastating earthquakes that have occurred in Turkey in the modern era. Teams of rescuers from 19 EU states quickly responded and carried out rescue missions across the affected area. This article is a report of a case series of rescues performed by the Romanian response team RO-USAR 1, with its aim being to assess the need of an internation consensus regarding immediate first-care in patients that are victims of natural or human-made catastrophes. Operations: A total of five victims were extracted alive from under the debris by our team and transported to the nearest available hospital by ambulance. A total of eight deceased victims were also extracted to facilitate access to the aforementioned alive victims. Conclusions: Quickly recognizing life-threatening situations and rapidly instating rapid fluid resuscitation is an essential step in reducing mortality in patients affected by major natural or human-made disasters. The need for an international consensus for the prehospital care of these patients is needed now more than ever in order to further ameliorate morbidity and mortality that largely occurs due to crush syndrome and its derived complications.